2019
DOI: 10.9734/mrji/2019/v27i630117
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocin Production by Lactobacillus plantarum NRIC 0383, Measured in Terms of Its Antagonistic Activity against Bacteria Pathogens of Selected Vegetables

Abstract: This study was carried out to measure the optimum condition for Bacteriocin production by Lactobacillus plantarum. Bacteriocin production with the candidate bacterium Lactobacillus plantarum NRIC 0383) was optimized by varying the incubation temperature and adjusting the pH of the production medium, whilst estimating bacteriocin production in terms of the antagonistic activity (zone of inhibition mm) against bacteria pathogens of selected vegetables using the well diffusion assay. Bacteriocin production was hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…At 45°C and 50°C no bacteriocin production was recorded. Ihum et al (2019) found that L. plantarum NRIC 0383 produce maximum bacteriocin at optimized temperature of 35°C. It was also reported that increase in temperature caused the decreased bacteriocin activity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…At 45°C and 50°C no bacteriocin production was recorded. Ihum et al (2019) found that L. plantarum NRIC 0383 produce maximum bacteriocin at optimized temperature of 35°C. It was also reported that increase in temperature caused the decreased bacteriocin activity.…”
Section: Discussionmentioning
confidence: 94%
“…lactis KT2W2L. Ihum et al (2019) revealed that pH 6 is the optimum pH for Lactobacillus plantarum NRIC 0383. Jana et al (2019) observed optimized bacteriocin production at pH 6.8.…”
Section: Discussionmentioning
confidence: 98%